Tissue expression of hsa-microRNA-3654 in male patients with external anogenital warts - Mohamed A.I. Elsayed; Moustafa M.K. Eyada; Shymaa A. Maher; Mohamed Azab (Journal of the Egyptian Women’s Dermatologic Society)
Background Human papillomavirus (HPV) infection is common across the world’s population, with millions of new cases reported each year. An increasing number of disorders are being linked to dysregulated microRNA (miRNA) expression, particularly when high-risk human papillomavirus infection is present. Objective To investigate the miR-3654 expression level in male patients with anogenital warts (AGWs) to develop a new patho-physiolological era in the genital wart. Patients and methods A total of 25 male patients with AGWs were consecutively enrolled in this case control study. MiR-3654 expressions in lesional skin and nonlesional skin were detected by quantitative PCR. Results Diseased tissue had a significantly lower median of miR-3654 level than normal healthy skin. There was no significant correlation between diseased tissue miR-3654 level with patient’s age, number of lesions, and average size of lesions. Conclusion It was found that diseased tissue miR-3654 was downregulated in warts compared with normal skin. Given its predicted targets and functions, the current study findings point out that miR-3654 could be a potential disease biomarker and may play a regulatory role in pathogenesis of AGWs.